2002
DOI: 10.1055/s-2002-20518
|View full text |Cite
|
Sign up to set email alerts
|

Size at Birth, Fat-Free Mass and Resting Metabolic Rate in Adult Life

Abstract: Resting metabolic rate is an important predictor of obesity and is closely related to fat-free mass. There is evidence that fat-free mass may be partly determined during critical periods of growth before and after birth. The objective of this study was to examine the relationship between size at birth, childhood growth and fat-free mass and resting metabolic rate in adult life. 318 men and women with detailed records of body size at birth and growth during school years participated in the study. Fat-free mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 5 publications
4
68
0
3
Order By: Relevance
“…It has been suggested that the association between birth weight and BMI in cohorts older than those studied in the present study could be related to more muscle mass developed at a critical period in foetal life close to week 30 in utero as well as during childhood. 23 That theory is supported by an association between birth weight and fatfree mass in adulthood at any adult BMI, 23 and an inverse relation between birth weight and adult truncal fat. 22 This indicates the weakness of BMI as a measure of body composition or body fatness.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been suggested that the association between birth weight and BMI in cohorts older than those studied in the present study could be related to more muscle mass developed at a critical period in foetal life close to week 30 in utero as well as during childhood. 23 That theory is supported by an association between birth weight and fatfree mass in adulthood at any adult BMI, 23 and an inverse relation between birth weight and adult truncal fat. 22 This indicates the weakness of BMI as a measure of body composition or body fatness.…”
Section: Discussionmentioning
confidence: 98%
“…21,22 The association is probably due to larger muscle mass developed in critical periods in foetal life and in childhood leading to higher birth weight and adult BMI in the cohorts from early in last century. 22,23 The prevalence of overweight and obesity has increased at all ages during the last decades. More knowledge is needed about the impact of size at birth on the growing generation's BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Foetal programming of lean body mass has been suggested in recent studies (Weyer et al, 2000;Eriksson et al, 2002;Singhal et al, 2003). It would have been desirable to include a measure of body composition at birth, such as arm circumference and skinfolds (Koletzko et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It would have been desirable to include a measure of body composition at birth, such as arm circumference and skinfolds (Koletzko et al, 2002). There is a critical period for muscle growth around 30 weeks in utero, and fat-free mass may be determined during critical periods of muscle growth in utero as well as during childhood (Eriksson et al, 2002). The mean BMI of women of childbearing age was 24.4 kg/m 2 in Iceland at the time of the study (Statistics Iceland, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These differences in body composition, associated with impaired glucose metabolism, may persist into adulthood, as suggested by studies from Finland 35 and from England using DEXA scan 36 , indicating that for the same BMI as age-matched controls, healthy elderly individuals born SGA have 3-5 kg less lean tissue mass, more fat mass, and a more central fat distribution. Similarly, studies from Denmark in cohorts of healthy young men born SGA indicate that they have slightly less lean tissue mass and slightly more body fat, but clearly higher abdominal fat mass 37 than age-matched controls of similar BMI, or that they showed reduced forearm glucose uptake 38 and reduced muscle expression of key proteins involved in insulin signalling and glucose transport.…”
Section: The Insulino-resistant 'Catch-up Fat' Phenotypementioning
confidence: 94%